Effects of Climatic Change On Gsm Signal in Lagos Metropolitan Terrain - O, Shoewu; L.A, Akinyemi; F.O, Edeko (Review of Environment and Earth Sciences, 2014)
The nexus of this study is to examine thoroughly the dependence of climatological parameters on GSM signal, especially in a metropolitan terrain. To validate this work, field measurements were carried out in the ITU regions of Lagos metropolitan area. The measurement system consisted of live documented radio base stations (BS) data transmitting at 13GHz, 15GHz and 23GHz in seven sites that constituted a metropolitan environment. The seven sites were segmented into non-urban (rural), suburban, urban, Ex-urban, dense-urban, micro-urban and peri-urban propagation environment. The Rain outage of the annual unavailability of the region of metropolitan data was collected using a Lenovo Laptop with installed path loss software alongside a licensed key called DONGLE. Results of this effort reveal that climate change affects signal propagation.